Shrubs plays an important role in configuration of shelterbelt in windy and sandy areas - Zhang, Shuai; Yuan, Weijie; Yu, Yi; Zhang, Yaoxiang; Wang, Weinan; Wang, Luzhen; Yang, Ying; Wang, Haixia (Frontiers in Ecology and Evolution, 2024)
Introduction Planted forests are of great significance in reducing wind erosion and controlling degraded land, and are the main measure to improve the ecological environment in arid and semi-arid areas. Afforestation is mainly based on tall trees, but forest belts consume a large amount of water, bringing significant pressure to the environmental carrying capacity. While shrubs generally consume less water than do trees, it remains understudied what role shrubs play in configuration of shelterbelts in arid areas. Methods In this study, we conducted wind tunnel simulation experiments with the common used afforestation tree species Populus popularis and shrub species Salix psammophila. We set up single- or double-belt pure forest and mixed tree/shrub configurations, to analyze their effects on the wind speed, flow field, and wind prevention efficiency of different forest belt types. Results The results showed that: 1) the wind erosion resistance of the double-belt shelter forest was stronger than that of a single-belt forest. 2) Shelterbelts consisting of trees had a strong resistance to airflow disturbances, but their protective effect was reflected mainly in the canopy layer, with poor near-surface protection. 3) Shelterbelts consisting of shrubs had a good protective effect within effective height, and the wind speed in the double-shrub forest belt was 77% of that in the single-tree forest belt. 4) The wind prevention efficiency within the shrub forest belt was better than that of the tree forest belt, with wind prevention efficiency exceeding 40% in most double-shrub forests. Shrubs as a supplement to trees could increase the minimum wind prevention efficiency by up to 30%. Discussion Therefore, the role of shrubs should be emphasized in afforestation in arid areas, especially in areas that need near-surface protection.